Eye Injuries in Combat Sports - Literature Review - Kozdra, Bartłomiej; Olszok, Mikołaj; Karbowiak, Krzysztof; Makselan, Natalia; Nawrat, Natalia; Handzel, Handzel; Antczyk, Antoni; Wijas, Daniel; Kluś, Michał (Quality in Sport, 2026)
Background: Eye injuries are an important cause of morbidity and can lead to permanent visual impairment, particularly in young, physically active individuals engaged in combat sports, where deliberate strikes to the head and face, close contact and full‑contact rules create a high‑risk environment for ocular trauma (Akanno et al., 2025; Doherty et al., 2025; Zachovajevas et al., 2025). Aim: To review and synthesize current evidence on the epidemiology, mechanisms, risk factors and discuss prevention strategies in the context of combat‑related ocular trauma. Materials and Methods: A narrative review with elements of a systematic search was conducted in PubMed (2000-2026) focusing on full‑contact and mixed combat disciplines. Priority was given to large epidemiological studies and systematic reviews on MMA and boxing injuries. Additional data were drawn from population‑based analyses of sports‑related eye injuries, retinal screening in collision sports and studies on combat ocular trauma. Results: In professional boxing and MMA, eye injuries accounted for roughly one‑third of all injuries mainly eyebrow/eyelid lacerations, orbital hematomas, and corneal abrasions; in boxing, eye injuries were linked to higher loss rates. Systematic reviews of MMA show 66.8-78% of injuries involve the head, often the orbital‑eyelid region. Population studies indicate that collision and combat sports are major sources of sports-related eye trauma in young males. Conclusions: Eye injuries in combat sports are frequent, clinically significant and likely underreported. Integrating IOC‑recommended ophthalmic screening and standardized surveillance with rule and equipment modifications, education and prompt specialist management-guided in part by experience from collision sports and combat ocular trauma-offers a rational framework to reduce visual morbidity in this population.